Automatically identifying the sentence skeleton of Chinese sentences based on the event model. - Xu, Wei; Zhao, Ke.; Yi, Zhenzhen; Li, Yatao; Cheng, Peitao
Many difficulties remain in identifying the sentence skeleton of Chinese sentences. The purpose of this paper is to automatically identify the sentence skeleton of Chinese sentences on the event level. Based on the event model, this paper discusses the relationship between events and concepts, and presents an event conceptualization method. It analyzes the event composition of Chinese sentences, classifies the relationships among events, and proposes a recursive description of the event composition of Chinese sentences. Based on these analyses, an algorithm for automatically identifying the sentence skeleton of Chinese sentences based on the event model is presented. The results of the final experiment show an 89% success rate, which demonstrates that the proposed algorithm is feasible and effective.
Keywords: Algorithm design and analysis; Sentence skeleton; Analytical models